Dementia in metaphors: A qualitative study among informal caregivers of people with dementia from migrant and ethnic minority groups - Anke J.M. Oerlemans; Aletta G. Dorst; Marjan L. Knippenberg; Gert J. Olthuis (Elsevier, 2023)
Introduction: People with dementia from migrant and ethnic minority (MEM) groups often receive suboptimal care. Differences in perceptions, values and preferences, and linguistic barriers may complicate communication between persons with dementia, their families and healthcare professionals. Metaphor analysis can provide unique insight into the lifeworld of people with dementia and their informal caregivers. This study identified the metaphors with which informal caregivers of persons with dementia from diverse cultural-linguistic backgrounds understand and discuss dementia. Methods: We conducted 7 focus groups (n ​= ​42) and 12 interviews (n ​= ​13) with informal caregivers of persons with dementia living in the Netherlands from six different cultural backgrounds: Dutch, Chinese, Turkish, Moroccan, Surinamese, and Dutch-Antillean. Interviews, in the native tongue of participants, were analyzed for the presence of direct and indirect metaphor. Results: The results indicate a conspicuous lack of metaphor to reflect on the nature and experience of having dementia. Two typical conceptual metaphors in health communication (journey/war) are virtually absent in all MEM groups. Furthermore, results suggest a one-sided and negative outlook on dementia, with an emphasis on persons with dementia as 'childlike' or 'crazy'. Conclusion: Our results suggest a lack of extensively available sophisticated (metaphorical) language to consider daily life with persons with dementia. There is a clear need to address the stigma and lack of medical knowledge surrounding dementia in these MEM groups and to carry out more cross-linguistic and cross-cultural research to explore which metaphors aid understanding and lead to the empowerment and restoration of self-worth of people with dementia.